DEVELOPMENT AND VALIDATION OF UV-VISIBLE SPECTROSCOPIC METHOD FOR ESTIMATION OF CARBAMAZEPINE IN BULK AND TABLET DOSAGE FORM - Zadbuke, Nityanand; Shahi, Sadhana; Jadhav, Ajit; Borde, Santosh (International Journal of Pharmacy and Pharmaceutical Sciences, 2016)
Objective: To develop and validate simple, accurate, rapid, precise, reproducible and cost effective spectrophotometric method for the quantitative estimation of carbamazepine in a pharmaceutical formulation. Methods: The developed UV spectrophotometric method for the quantitative estimation of carbamazepine is based on measurement of absorption at maximum wavelength 284 nm using methanol as a solvent. The stock solution of carbamazepine was prepared, and subsequent suitable dilution was prepared in distilled water to obtained standard curve. The standard solution of carbamazepine shows absorption maxima at 284 nm. Results: The drug obeyed beer lambert's law in the concentration range of 2-14 Âµg/ml with regression 0.9997 at 284 nm. The overall % recovery was found to be 99.99% which reflects that the method was free from the interference of the impurities and other excipients used in the formulation. The low value of % RSD was indicative of accuracy and reproducibility of the method. The % RSD for inter-day and intra-day precision was found to be 0.1568 and 0.1746 respectively which is<2% hence proved that method is precise. Conclusion: The results of analysis have been validated as per International Conference on Harmonization (ICH) guidelines. The developed method can be adopted in routine analysis of carbamazepine in tablet dosage form as well bulk dosage form. Keywords: Carbamazepine, UV Spectrophotometry, Method development, Validation, ICH guidelines, Methanol.